Sustainable fuel aviation infrastructure and transition: hybrid agent-based modeling and system dynamics - Shoaib, Mohammad; Camelia, Fanny; Asmelash, Mebrahitom; Zaidi, Yaseen; Tantawy, Ashraf; Marr, Ian (Institute of Electrical and Electronics Engineers (IEEE), 2025)
The adoption of sustainable fuels in aviation, such as Sustainable Aviation Fuels (SAF), hydrogen (LH2), and ammonia (NH3), is a significant step toward achieving green and sustainable air transport. However, transitioning the aviation industry to sustainability is a complex process that requires an integrated transformation of both technological and social systems. With multiple potential fuel alternatives, it is important to identify the most viable fuel pathways. This paper presents the concept of a hybrid, Agent-Based Modeling (ABM) and modular System Dynamics (SD) model, developed as a computational framework to analyze the interactions among technology, industry, markets, and society. A hybrid ABM and SD approach is an ideal choice for analyzing the transition of the ATS to sustainable fuels because of the complexity of the problem, which involves various entities with distinct behaviors and decision-making processes. The modular SD model consists of multiple stock and flow modules of passenger demand, aircraft orders, fleet development, fuel demand, sustainable fuel production, and infrastructure, providing a holistic but detailed, granular analysis of interactions and impacts within the system. The ABM approach facilitates the integration of SD modules by incorporating agents such as airlines, fuel suppliers, airports, aircraft manufacturers, and fuel producers, each with their unique behaviors. The proposed model serves as a reference framework for simulation and analysis, supporting future research on aviation sustainability and providing a decision support tool for understanding the long-term feasibility of different sustainable aviation fuels.
Keywords: Agent-Based Modeling (ABM); Causal Loop Diagram (CLD); hybrid modeling; System Dynamics (SD); Sustainable Aviation Fuels (SAF); aviation energy transition; simulation